Delineating management zones for precision agriculture applications: a case study on wheat in sub-tropical Brazil - Melo Damian, Júnior; De Castro Pias, Osmar Henrique; Santi, Antônio Luis; Di Virgilio, Nicola; Berghetti, Juliano; Barbanti, Lorenzo; Martelli, Roberta (Italian Journal of Agronomy, 2016)
In sub-tropical Brazil, the wheat (Triticum aestivum L.) crop requires identification of pending constraints as premise for grain yield (GY) increases. In this light, spatial variation of soil properties and their relationship with GY were investigated in a case study, where the delineation of homogeneous zones could lead to site-specific management in view of crop improvement. In 2012, twelve chemical and physical soil attributes, GY and the three yield components (spikes per square meters, grains per spike, grain weight) were geo-referentially assessed in a 50×50 m grid in a 4.7 ha wheat field. GY exhibited a modest mean (2.61 Mg ha–1), associated with a noticeable variation (CV, 17.4%). A multiple stepwise regression of soil carbon (C) and pH explained a high share of GY variation (R2, 0.83**). Maps of C, pH and GY obtained through inverse distance weighting showed the spatial trends of the three traits. C and pH clustering delineated three homogeneous zones at respective low, intermediate and high levels of C, pH, and also GY, setting the premise for a differential management of crop inputs. In particular, a significant part (21.8%) of field surface featured very low GY (2.05 Mg ha–1); thus substantial yield increase could be envisaged through targeted supply of organic amendments (soil C, 14.1 g dm–3), and especially lime (soil pH, 4.92). A larger field portion (54%) showed intermediate GY (2.65 Mg ha–1), C (15.3 g dm–3) and pH (5.23), deserving a lesser degree of amelioration. The remaining 24.2% of field surface exhibited the highest GY (3.16 Mg ha–1), C (17.2 g dm–3) and pH (5.46). Based on the difference between GY registered in the low vs. high zone, overcoming soil constraints could be credited with a remarkable (>50%) yield increase, although further years of wheat cropping would be needed to prove the consistency of the two temporally stable soil traits, C and pH, as yield determinants. Nevertheless, this case study addressing a world area that features very different conditions from wheat grown in temperate regions shows good prospects for variable application of crop inputs in the frame of precision agriculture techniques.